Studi Potensi Keberlanjutan Transportasi Umum Di Belinyu Kabupaten Bangka - Teddy Sanjaya; Hafsah Hafsah; Devi Jum’atika; Desy Yofianti (Universitas Mercu Buana, 2022)
Public transportation has significant role to regulates human mobility to be effective. But, people in Belinyu has low interest towards public transportation. Public transportation is now decreasing and the malfunction terminal cause the appearance of phantom terminal. This research is to analyze the sustainability of public transportation in Belinyu. The data was obtain from distribution of questionnaire to passengers and drivers, interview for the owner of public transportation company, Belinyu District Office, and Bangka District Transportation Office. There are 407 passenger respondents who came from 12 villages in Belinyu with 45,193 population. The sustainability of public transportation in Belinyu can be determined from the indicators with SPSS (Statistical Product and Service Solutions) analyze which divisible from 4 quadrant. Indicators with percentage more than 50% (satisfying) are the depature accuracy (61%), public transportation condition (63%), pleasurable (57%), safety (56%), and fee (61%). The main indicators with 10% percentage are the existence of public transportation ang supporting facilities. From the results, public transportation in Belinyu still has the sustainability potential but it needs improvement of terminal service and public transporation existence, because this indicators are not enough for fill up the respondents satisfaction.